An Inconvenient Truth: Why Social Policies Might Fail - Dimas Suryo Sudarso (Kementerian Perencanaan Pembangunan Nasional (Bappenas), 2019)
Developing countries implemented social policies after suffered by economic and financial crisis. Social policies, such as conditional cash transfer, non-contributory social insurance policy, and energy subsidy, were introduced to improve the well-being of the society. However, these policies potentially fail and prevent these countries to converge to be developed countries, due to low level of human capital formation, increased informal employment, unsustainable fiscal capabilities, the induction of “pork-barrel politics” in the policy planning and formulation process, and reduced incentive to work. This essay also provided recommendation on social policies improvement. Thus, policymakers able to increase the effectiveness of current social policies to maintain the country’s objective in reducing income inequality, without hampered the country’s productivity and economic growth.